Alban Berg's Lulu - Naude Janet Joan (College of Music, 2024)
This study is an analysis of the opera, Lulu, by Alban Berg, Concentrating on pitch organisation in relation to its dramatic context. An introduction cutlines Iulu' s conception, posthomous, history, libretto and Dramatic Persona. The first chapter represents an exposition of the opera's basic material. It includes a description of Berg's early and later row-derivations, and analysis of the Prologue, Schon's Sonata, alwa's Recitative-review and the Chorale, from Act I. The second chapter consists of a selection of numbers, demonstrating development towards the musical and dramatic climax of the work. This is exemplified by Geschwitz's Recitative, Schon's Arietta, 'Turrnltuoso, the exposition of Alwa's Rondo, Schon's Aria, Lulu's Lied, Schon's death and the Film Music, from Act II/1. The third chapter illustrates recapitulation of the opera's first half, by rreans of the Rondo's completion and Alwa 's Hymn, Lei tsektionen and role doubling, and Variations on Wedekind's lute rrelcdy, from Acts II/2 and III. Each chapter contains synopses of dramatic events 1n relation to the opera's formal design, to describe the context in which the analysed excerpts appear.